PENGARUH INKLUSI KEUANGAN DAN AKSES TEKNOLOGI DIGITAL TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PENDIDIKAN EKONOMI DI UNIVERSITAS NEGERI MEDAN - Kristin Margaretha Simarmata; Fitrawaty (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to determine the influence of financial inclusion and access to digital technology on the financial management of Economics Education students at Medan State University. This study employed a quantitative approach with an ex post facto design. Primary data were collected through questionnaires distributed to 132 Economics Education students from the 2022 and 2023 cohorts using total sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics 26. The results showed that financial inclusion had a positive and significant effect on student financial management (p = 0.000 < 0.05). Access to digital technology also had a positive and significant effect on student financial management (p = 0.002 < 0.05). Simultaneously, financial inclusion and access to digital technology had a positive and significant effect on student financial management (p = 0.000 < 0.05). The coefficient of determination (R²) was 0.268, indicating that financial inclusion and access to digital technology explained 26.8% of the variation in student financial management, while the remaining 73.2% was explained by other factors. Keywords: financial inclusion; digital technology access; financial management Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh inklusi keuangan dan akses teknologi digital terhadap pengelolaan keuangan mahasiswa Pendidikan Ekonomi Universitas Negeri Medan. Penelitian ini menggunakan pendekatan kuantitatif dengan desain ex post facto. Data primer dikumpulkan melalui penyebaran kuesioner kepada 132 mahasiswa Pendidikan Ekonomi angkatan 2022 dan 2023 yang dipilih menggunakan teknik total sampling. Analisis data dilakukan dengan menggunakan regresi linear berganda melalui bantuan IBM SPSS Statistics 26. Hasil penelitian menunjukkan bahwa inklusi keuangan berpengaruh positif dan signifikan terhadap pengelolaan keuangan mahasiswa (p = 0,000 < 0,05). Akses teknologi digital juga berpengaruh positif dan signifikan terhadap pengelolaan keuangan mahasiswa (p = 0,002 < 0,05). Secara simultan, inklusi keuangan dan akses teknologi digital berpengaruh positif dan signifikan terhadap pengelolaan keuangan mahasiswa (p = 0,000 < 0,05). Nilai koefisien determinasi (R²) sebesar 0,268 menunjukkan bahwa inklusi keuangan dan akses teknologi digital mampu menjelaskan 26,8% variasi pengelolaan keuangan mahasiswa, sedangkan sisanya sebesar 73,2% dipengaruhi oleh faktor lain di luar penelitian. Kata kunci: inklusi keuangan; akses teknologi digital; pengelolaan keuangan